Uso de modelos pedagógicos y didácticos en los procesos educativos utilizando las tic’s para el aprendizaje de los docentes de la unidad educativa “José Rodríguez Labandera” año 2016. - Huacón García, Cecilia Margoth (2016)
The use of ICT permeates all aspects of social and economic life. These technologies are evolving at a fast pace. Its continuous practice requires constant updating of knowledge and experience. Adaptation is only possible if one has a solid knowledge of the principles and concepts of this area. In the step with the development of technologies and skills in the evolution of education, it is required that teachers require an education program taking into account the latest advances in the field and appropriate training teachers. The rapid evolution of ICTs is a source of difficulties for educational establishments. The wide range of primary and secondary teachers also face these permanent transformations. The proposed curriculum is designed to facilitate your task with this trend and in situations in perpetual change. It aims to help educational authorities to develop ICT policy in a methodical and controlled manner as in the secondary education of the Educational Unit "José Rodríguez Labandera", to integrate in a rational and efficient way in their programs the use of Tic's, even if they start from scratch. Having a pedagogical model also proves to be useful for organizing a teacher training plan that will also allow the structuring of a curriculum. Vocational training is essential for those who are beginning to use Tic's in teaching. For this, different approaches are identified for the development of ICTs, it helps to define the framework of a training for the teaching staff of the Educational Unit "José Rodríguez Labandera".